THE GROUNDS OF KNOWLEDGE: A COMPARISON BETWEEN KUHN’S PARADIGMS AND FOUCAULT’S EPISTEMES (Revista Kriterion, 2021)
Thomas Kuhn’s “paradigms” and Michel Foucault’s “epistemes” are often seen as similar concepts, in that both would establish necessary conditions of knowledge. However, how close are they to each other? The aim of this article is to compare these two concepts in detail. Firstly, I discuss the similarities and differences between paradigms and epistemes regarding a number of aspects, as well as their respective functions within Kuhn’s and Foucault’s approaches. The analysis is organized around a series of topics, such as “definition” and “scope,” with the intention of facilitating the comparison. Next, I examine some comments that Foucault and Kuhn made on each other’s work, paying particular attention to matters related to the nature and role of paradigms and epistemes.